2011
DOI: 10.1007/s10584-011-0200-z
|View full text |Cite
|
Sign up to set email alerts
|

Climatic trends and impact of climate change on agriculture in an arid Andean valley

Abstract: Little is known about climate change and its impacts for the arid coastal and mountainous regions in northern Chile. The Elqui river basin, part of the Norte Chico of Chile between 27ºS and 33ºS latitude, is located south of the hyper-arid Atacama desert. Despite water scarcity, agricultural development in this region has been enhanced by agronomic practices and the marketing of valuable products. This paper characterizes the actual climate conditions and presents an overview and analyses of past climate varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…In both, spring and summer hydrological droughts were found in the upstream and naturalised scenario, whereas winter droughts were mainly seen in the downstream (post-dam) and human-influenced scenario. This shift in the timing of droughts due to human-influences is an important deviation from the natural system as it can have implications on ecosystem response and resilience to drought, especially in arid climates where ecosystems are already sensitive to small changes in precipitation and available water (Fiebig-Wittmaack et al, 2012). These results are in agreement with existing studies which found that reservoirs modify the hydrologic regime of rivers, producing a delay of the natural annual cycle of river and provide a buffering capacity (Petts & Gurnell, 2005;López-Moreno et al 2009;Assani et al, 2013) due to increased storage.…”
Section: Drought Characteristics In Modelled Datamentioning
confidence: 99%
“…In both, spring and summer hydrological droughts were found in the upstream and naturalised scenario, whereas winter droughts were mainly seen in the downstream (post-dam) and human-influenced scenario. This shift in the timing of droughts due to human-influences is an important deviation from the natural system as it can have implications on ecosystem response and resilience to drought, especially in arid climates where ecosystems are already sensitive to small changes in precipitation and available water (Fiebig-Wittmaack et al, 2012). These results are in agreement with existing studies which found that reservoirs modify the hydrologic regime of rivers, producing a delay of the natural annual cycle of river and provide a buffering capacity (Petts & Gurnell, 2005;López-Moreno et al 2009;Assani et al, 2013) due to increased storage.…”
Section: Drought Characteristics In Modelled Datamentioning
confidence: 99%
“…Most precipitation (80%) is concentrated in the three austral winter months (JuneAugust) (Bourgin et al, 2012). Recent studies have shown that the dry Andes are currently warming (Falvey and Garreaud, 2009) and that precipitation may decrease or remain stable in the future (Fiebig-Wittmaack et al, 2011).…”
Section: Study Areamentioning
confidence: 99%
“…The existence and development of several mining projects near the headwaters of the main transverse valleys in the region also contribute to the reginal economy but raises environmental and resource equity disputes (Oyarzún and Oyarzún, 2011;Kronenberg, 2013). There is a strong concern that the observed (Falvey and Garreaud, 2009) and predicted (Cabré et al, 2016;Bozkurt et al, 2017) warming trend in the high Andes together with the apparent decreasing precipitation over recent decades (Fiebig-Wittmaack et al, 2012;Quintana and Aceituno, 2012;Schulz et al, 2012) could result in aggravated water stress in the Norte-Chico region. This in turn could exacerbate inter-sector conflicts about water usage and limit future development (Young et al, 2010;Valdés-Pineda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%